(untitled) (Thành phố Hồ Chí Minh, 2014)
As far as this book is concerned, it is arranged into 24 units with a total of five chapters whose themes centre upon the three parts of the IELTS Speaking test. Especially, questions which are typical in the IELTS Speaking test are provided so that you can be well prepeared for your actual test in the near future.
Keywords: English language,Ngôn ngữ Anh,English language,Ngôn ngữ Anh; Spoken English,Nói tiếng Anh